Inter-laboratory comparison of three earplug fit-test systems. - Byrne, David C.; Murphy, William J.; Krieg, Edward F.; Ghent, Robert M.; Michael, Kevin L.; Stefanson, Earl W.; Ahroon, William A. (Journal of Occupational & Environmental Hygiene, 2017)
The National Institute for Occupational Safety and Health (NIOSH) sponsored tests of three earplug fit-test systems (NIOSH HPD Well-Fit, Michael & Associates FitCheck, and Honeywell Safety Products VeriPRO). Each system was compared to laboratory-based real-ear attenuation at threshold (REAT) measurements in a sound field according to ANSI/ASA S12.6-2008 at the NIOSH, Honeywell Safety Products, and Michael & Associates testing laboratories. An identical study was conducted independently at the U.S. Army Aeromedical Research Laboratory (USAARL), which provided their data for inclusion in this article. The Howard Leight Airsoft premolded earplug was tested with twenty subjects at each of the four participating laboratories. The occluded fit of the earplug was maintained during testing with a soundfield-based laboratory REAT system as well as all three headphone-based fit-test systems. The Michael & Associates lab had the highest average A-weighted attenuations and smallest standard deviations. The NIOSH lab had the lowest average attenuations and the largest standard deviations. Differences in octave-band attenuations between each fit-test system and the American National Standards Institute (ANSI) sound field method were calculated (Attenfit-test- AttenANSI). A-weighted attenuations measured with FitCheck and HPD Well-Fit systems demonstrated approximately ±2 dB agreement with the ANSI sound field method, but A-weighted attenuations measured with the VeriPRO system underestimated the ANSI laboratory attenuations. For each of the fit-test systems, the average A-weighted attenuation across the four laboratories was not significantly greater than the average of the ANSI sound field method. Standard deviations for residual attenuation differences were about ±2 dB for FitCheck and HPD Well-Fit compared to ±4 dB for VeriPRO. Individual labs exhibited a range of agreement from less than a dB to as much as 9.4 dB difference with ANSI and REAT estimates. Factors such as the experience of study participants and test administrators, and the fit-test psychometric tasks are suggested as possible contributors to the observed results.